Nation-state Level of Analysis of North Korea’s Foreign Policy on Nuclear Deterrence - Adebolu-Ololade, Toluwanimi Esther; Iloh, Emeka C. (Journal of Contemporary International Relations and Diplomacy, 2022)
North Korea became a nuclear weapon state in 2006 and has vehemently pursued and advanced its nuclear weapons program against the desires of the international community with claims that its policy on nuclear deterrence is to deter enemy states from attacking. Hence, the issue has been a source of debate in recent years. The study therefore conducted an analysis of North Korea’s foreign policy on nuclear deterrence using the nation state level of foreign policy analysis to better understand the foreign policy decision. The study found that states peculiarities such as the type of government, bureaucracy, military capacity, identity and ideology, national interest, location and national resources, population, public opinion, and economic capacity among others, can influence a state’s foreign policy decision-making. The study concludes that despite the authoritarian leadership in North Korea, all these other elements and characteristics within the state actively shape North Korea’s foreign policy on nuclear deterrence.